Evaluation of Online Learning for the Public Ethics Training Course for CPNS Batch I Tanjung Jabung Barat Regency 2020 - Lailatul Isnaini (Jurnal Prajaiswara, 2021)
This article aims to explain online learning in the latsar CPNS since the COVID-19 outbreak. The research method uses a pre-test and a post-test. The number of samples is set at 40 respondents. Data was collected through an open survey technique with a questionnaire-assisted instrument form Google. Analysis data is used as quantitative descriptive. The results of the study showed that the implementation of online learning had been carried out well amid the COVID-19 pandemic. The conclusion is an online learning model that is quite effective and can be used as a learning medium accompanied by a pandemic. In addition, as an immediate policy on education costs must be carried out, which is the impact of COVID-19.